2017
DOI: 10.1007/s11661-017-4386-1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Lattice Distortion to Solid Solution Strengthening in a Series of Refractory High Entropy Alloys

Abstract: We present an experimental approach for revealing the impact of lattice distortion on solid solution strengthening in a series of body-centered (bcc) Al-containing, refractory high entropy alloys from the Nb-Mo-Cr-Ti-Al system. By systematically varying the Nb and Cr content, a wide range of atomic size difference as a common measure for the lattice distortion was obtained. Single phase, bcc solid solutions were achieved by arc-melting and homogenization as well as verified by means of scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 27 publications
2
59
0
1
Order By: Relevance
“…Although the high-throughput idea is not new for HEAs 6 , 17 , CALPHAD simulations, for example, are a high-throughput method for predicting phase equilibria that are used in HEA alloy design 6 , 10 , 18 . Alloying 19 and microstructural 20 evolution have also been linked to strength, but we could not find an example of targeted alloy design for the prediction of HEA solid solution strengthening, the key strengthening mechanism in these alloys, in which a significantly stronger composition was designed based upon prediction . Studies exist that show stronger compositions are not necessarily the ones with the highest entropy, and these alloys are also not necessarily equiatomic 21 .…”
Section: Introductionmentioning
confidence: 98%
“…Although the high-throughput idea is not new for HEAs 6 , 17 , CALPHAD simulations, for example, are a high-throughput method for predicting phase equilibria that are used in HEA alloy design 6 , 10 , 18 . Alloying 19 and microstructural 20 evolution have also been linked to strength, but we could not find an example of targeted alloy design for the prediction of HEA solid solution strengthening, the key strengthening mechanism in these alloys, in which a significantly stronger composition was designed based upon prediction . Studies exist that show stronger compositions are not necessarily the ones with the highest entropy, and these alloys are also not necessarily equiatomic 21 .…”
Section: Introductionmentioning
confidence: 98%
“…Han et al have successfully synthesized TiNbMoTaW and TiVNbMoTaW refractory HEAs. It is found that the addition of Ti with the largest atomic size significantly improves the mechanical properties of HEAs at room and elevated temperature [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…41 Figure 1. Yield strength (σ 0.2 ) of several refractory high-entropy alloys [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (HEAs) and conventional stainless steel, aluminum, titanium, and nickel-based alloys. As potential high-temperature materials for structural applications, the HEAs show greater strength.…”
Section: Why Metal Mixology?mentioning
confidence: 99%